2015
DOI: 10.2350/15-11-1733-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Reference Range of Platelet Delta Granules in the Pediatric Age Group: An Ultrastructural Study of Platelet Whole Mount Preparations from Healthy Volunteers

Abstract: This study sought to determine delta granule normal ranges for children and to validate methodology for the appropriate diagnosis of delta granule deficiency (storage pool disease) by using the whole-mount technique in electron microscopy. Specimens obtained from 40 healthy volunteers (2 months of age through 21 years old, 21 females and 19 males) were tested. Results showed dense granules/platelet (DG/Plt) ranged from 1.78 to 5.25. The 5th percentile was 1.96 DG/Plt with an overall mean ± SEM 3.07 ± 0.12 DG/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…Using PEM alone to establish the diagnosis has recently become controversial, and the average granules per platelet in our cohort is near the observed average in healthy pediatric patients . Sorokin et al concluded a new diagnostic threshold of 2 dg/pl would in fact be more specific, but guaranteed to be less sensitive, proven by our study population as this value would have diagnosed merely 31% of our study population.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Using PEM alone to establish the diagnosis has recently become controversial, and the average granules per platelet in our cohort is near the observed average in healthy pediatric patients . Sorokin et al concluded a new diagnostic threshold of 2 dg/pl would in fact be more specific, but guaranteed to be less sensitive, proven by our study population as this value would have diagnosed merely 31% of our study population.…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, PEM results are difficult to interpret irrespective of the use of a more theoretically specific cutoff such as <2 dg/pl or the more sensitive cutoff of <3.68 dg/pl. In our population, PEM did not show any correlation to the patient's age, which has yet to be observed in the pediatric population . Given a lack of consensus regarding the reference range for PEM in pediatric patients, clinical research consideration should be given to flow cytometry in either establishing or confirming a δ‐SPD diagnosis since our current strategies inadequately classify patients .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Qualitative platelet dysfunction was diagnosed when there was impaired aggregation to one or more agonists (except isolated epinephrine defects) or impaired ATP secretion with reproducible findings on ≥2 occasions . A cut‐off of 2 or fewer dense granules/platelets was used as a diagnostic cut‐off to diagnose platelet storage pool disorders . Clotting factor deficiency was defined when a clotting factor level was below the age‐based reference range.…”
Section: Methodsmentioning
confidence: 99%
“…19 A cut-off of 2 or fewer dense granules/platelets was used as a diagnostic cut-off to diagnose platelet storage pool disorders. 20 Clotting factor deficiency was defined when a clotting factor level was below the agebased reference range. Thrombocytopenia was defined as platelet count <150/cumm.…”
Section: Haemostatic Defectsmentioning
confidence: 99%